Genome-wide analysis of LPS-induced inflammatory response in the rat ventral hippocampus: Modulatory activity of the antidepressant agomelatine. (4th July 2018) - Rossetti, Andrea Carlo; Paladini, Maria Serena; Racagni, Giorgio; Riva, Marco Andrea; Cattaneo, Annamaria; Molteni, Raffaella
Abstract: Objectives: Several studies reported that antidepressant drugs have immune-regulatory effects by acting on specific inflammatory mediators. However, considering the highly complex nature of the inflammatory response, we have adopted an unbiased genome-wide strategy to investigate the immune-regulatory activity of the antidepressant agomelatine in modulating the response to an acute inflammatory challenge. Methods: Microarray analysis was used to identify genes modulated in the ventral hippocampus of adult rats chronically treated with agomelatine (40 mg/kg, os) before being challenged with a single injection of lipopolysaccharide (LPS; 250 μg/kg, i.p.). Results: The administration of LPS induced the transcription of 284 genes mainly associated with pathways related to the immune/inflammatory system. Agomelatine modulated pathways not only connected to its antidepressant activity, but was also able to prevent the activation of genes induced by LPS. Further comparisons between gene lists of the diverse experimental groups led to the identification of a few transcripts modulated by LPS on which agomelatine has the larger effect of normalisation. Among them, we found the pro-inflammatory cytokine Il-1β and, interestingly, the metabotropic glutamatergic transporter Grm2 . Conclusions: These results are useful to better characterise the association between depression and inflammation, revealing new potential targets for pharmacological intervention for depression associated to inflammation.